2013
DOI: 10.21101/cejph.a3795
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Trends in Southeastern Serbia

Abstract: SUMMARYThe aim of the study was to assess recent changes in lung cancer incidence and mortality trends in the male and female population in Southeastern Serbia, in the period 1999-2008. Data used for analyses were provided by the Cancer Registry of the Institute for Public Health, Niš. Incidence and mortality trends were based on crude and age-standardized incidence and mortality rates for the period 1999-2008. Standardized rates were calculated by the direct method of standardization (per 100,000), using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to statistics, among the number of lung cancer cases in Serbia of southeastern Europe, the incidence rates in men were higher than those of women and the mortality rates of male patients were four times higher than those of female patients. This may be due to the smoking habit in males (2). According to the histological type of lung cancer, it can be divided into small cell lung cancer and non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics, among the number of lung cancer cases in Serbia of southeastern Europe, the incidence rates in men were higher than those of women and the mortality rates of male patients were four times higher than those of female patients. This may be due to the smoking habit in males (2). According to the histological type of lung cancer, it can be divided into small cell lung cancer and non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, lung cancer incidence among men exceeds that in women with a male: female incidence gender ratio of 3.1:1, a result which had been reported in most nations. 19 In Serbia, the gender ratio (males to females) of lung cancer incidence was reported to be 4:1, 20 In Ardabil, Iran 21 4.6:1, Saudi Arabia 3.9:1, Kuwait 3.0:1, and the United Arab Emirate 2.8:1. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Age as a risk factor for malignancies is well documented; it reflects intensity and long term exposure to risk factors such as lifestyle behaviors, particularly smoking. 20 Smoking is the leading cause of lung cancer and it was reported that 85-90% of lung cancer patients had a history of current or passive smoking. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Despite the immense efforts employed at the development of molecular targeted drugs, few efficient long-term therapeutic strategies for the advanced stages of LC exist due to fast-developing resistance 6. In Serbia, high unfavourable LC incidence and mortality trends showed a clear failure in primary and secondary prevention 7. Thus, earlier detection of LC would significantly improve outcomes and reduce the mortality burden.…”
Section: Introductionmentioning
confidence: 99%